2011
DOI: 10.1111/j.1420-9101.2011.02350.x
|View full text |Cite
|
Sign up to set email alerts
|

Postmating isolation and genetically variable host use in ecologically divergent host forms of Neochlamisus bebbianae leaf beetles

Abstract: Ecological speciation studies have more thoroughly addressed premating than postmating reproductive isolation. This study examines multiple postmating barriers between host forms of Neochlamisus bebbianae leaf beetles that specialize on Acer and Salix trees. We demonstrate cryptic isolation and reduced hybrid fitness via controlled matings of these host forms. These findings reveal host‐associated postmating isolation, although a nonecological, ‘intrinsic’ basis for these patterns cannot be ruled out. Host pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…In the present study, we demonstrated that multiple populations of both gall-former species, inhabiting either of two closely related oak species, express strong preferences for their natal host plant species. Our results are consistent with partial habitat isolation evolving in these gall wasps as a by-product of adaptation to different hosts, as has now been demonstrated to be an important component to reproductive isolation in a number of plant–insect systems ( Timema stick insects [50], leaf beetles [7], [54], pea aphids [55], ladybird beetles [56], Rhagoletis fruit flies [6], and Eurosta galling flies [49]). …”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we demonstrated that multiple populations of both gall-former species, inhabiting either of two closely related oak species, express strong preferences for their natal host plant species. Our results are consistent with partial habitat isolation evolving in these gall wasps as a by-product of adaptation to different hosts, as has now been demonstrated to be an important component to reproductive isolation in a number of plant–insect systems ( Timema stick insects [50], leaf beetles [7], [54], pea aphids [55], ladybird beetles [56], Rhagoletis fruit flies [6], and Eurosta galling flies [49]). …”
Section: Discussionsupporting
confidence: 90%
“…(5b) Hybrids between these host forms exhibit reduced growth rate and survivorship than the parental types do on their native hosts [41,47].…”
Section: From Host Forms To Host Racesmentioning
confidence: 99%
“…(5a) Each host form grows faster and survives better on its native host than on the host of the other host form [35,41,47].…”
Section: From Host Forms To Host Racesmentioning
confidence: 99%
“…In our study, the inherited pattern for host use depended not only on the cross, but the preference of the maternal species. A growing body of literature suggests that for herbivorous insect species, mothers have been shown to influence host use (Amarillo-Suarez & Fox 2006; Egan et al 2011; Cahenzli & Erhardt 2013). Egan et al (2011) specifically demonstrated that host-use and performance are traits with sex-linked maternal influence.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature suggests that for herbivorous insect species, mothers have been shown to influence host use (Amarillo-Suarez & Fox 2006; Egan et al 2011; Cahenzli & Erhardt 2013). Egan et al (2011) specifically demonstrated that host-use and performance are traits with sex-linked maternal influence. Consequently, the pattern of host specificity in hybrid crosses can be hard to predict since it will depend not only on the amount of genetic variation across a suite of traits, but also parental influence.…”
Section: Discussionmentioning
confidence: 99%